2008
DOI: 10.1016/j.dnarep.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of DNA damage/DNA repair capacity by XPC polymorphisms

Abstract: XPC, a key protein in the nucleotide excision repair (NER) pathway, recognizes damaged DNA and initiates NER. Genetic variations in the XPC gene might be associated with altered DNA repair capacities (DRC). In this study, we genotyped three XPC polymorphisms, Ala499Val (C→T), PAT (-/+) and Lys939Gln (A→C), and measured the DNA damage/DRC by alkaline comet assay challenged by BPDE and gamma-radiation in 476 healthy subjects. We also evaluated the associations between DNA damage/DRC and genotypes of XPC polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 42 publications
3
56
0
1
Order By: Relevance
“…The 3 most common polymorphisms reported in the literature and associated with cancer development are the alanine-to-valine substitution at codon 499 (Ala499Val; rs2228000), PAT (À/þ), and the lysine-toglutamine substitution at codon 939 (Lys939Gln; rs2228001). 21 We tested 7 XPC SNPs in total, which included the 3 most common XPC SNPs. Three intronic XPC SNPs from our panel (XPC-PAT, rs3731108, and rs1124303) were associated with prolonged PFS, possibly suggesting improved platinum sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3 most common polymorphisms reported in the literature and associated with cancer development are the alanine-to-valine substitution at codon 499 (Ala499Val; rs2228000), PAT (À/þ), and the lysine-toglutamine substitution at codon 939 (Lys939Gln; rs2228001). 21 We tested 7 XPC SNPs in total, which included the 3 most common XPC SNPs. Three intronic XPC SNPs from our panel (XPC-PAT, rs3731108, and rs1124303) were associated with prolonged PFS, possibly suggesting improved platinum sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of exon 12 results in the loss of function of XPC, leading to an increase in cancer development. [21][22][23][24] Our study indicated that patients with the XPC-PAT (þ/þ) genotype had decreased platinum sensitivity and worse PFS. This suggests a possible mechanism of how SNPs in intronic sequences can have effects on coding regions, ultimately leading to changes in protein and gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, functional studies for this polymorphism have also yielded inconsistent results. 26,27 Additional studies are required to evaluate the role of XPC variations in cisplatin response and ototoxicity.…”
Section: Dna Repair Gene Polymorphisms In Osteosarcoma Treatmentmentioning
confidence: 99%
“…These two polymorphisms involve changes in protein sequence [22,24] and have been associated with the risk of developing several cancers [25][26][27]. Moreover, experimental data [28,29] suggest that both the TA and the CC haplotypes result in protein variants that are less active in DNA repair than the CA wild-type. We found that the CA wild-type haplotype was associated with a favorable response to imatinib, as patients who carried one or two copies of such haplotype had a fourfold lower risk of achieving suboptimal response or failure to imatinib than the remainders.…”
Section: Discussionmentioning
confidence: 99%